Revision of the wingless pygmy grasshopper Potua Bolívar, 1887 (Orthoptera: Tetrigidae) from Southeast Asia - Muhammad, Amira Aqilah; Tan, Ming Kai; Puniamoorthy, Jayanthi; Adžić, Karmela; Deranja, Maks; Neo, Ivan; Loh, Rebecca Ker; Damit, Dayang Fazrinah Binti Awg; Japir, Razy; Chung, Arthur Y.c.; Suhaili, Awangku Shahrir Naqiuddin Awg; Gunsalam, Geofarry; et al. (Zootaxa, 2026)
Potua Bolívar, 1887, a genus currently assigned to Xerophyllini (Cladonotinae), requires taxonomic revision because its type species, P. coronata Bolívar, 1887, is poorly defined. It exhibits huge variability in the pronotum among type specimens and longstanding confusion with P. morbillosa (Walker, 1871). To resolve the issue, we performed morphometric analyses and sequenced a fragment of the cytochrome oxidase subunit I (COI) gene to reassess species boundaries. Integrating the morphological and genetic data, we synonymise P. coronata Bolívar, 1887, syn. nov. with P. morbillosa (Walker, 1871) and prove that specimens with different pronotal morphology, previously regarded as intraspecific variations, represent different species. Genetic variations within each morphotype are also very low. Here, we describe three new species—P. bulbosa Muhammad, Adžić & Tan, sp. nov. from the Malay Peninsula; P. kinabalu Muhammad & Tan, sp. nov.; and P. sepilok Tan & Muhammad, sp. nov. from Borneo. We also provide an annotated diagnostic table to distinguish each of the four species from Southeast Asia.